Analysis of the Current Situation and Influencing Factors of Touch Comfort Among Intensive Care Unit Nurses - Yuan Z; Liu C; Zhang K; Gao L; Sun S (Journal of Multidisciplinary Healthcare)
Zheng Yuan,1 Chunxia Liu,2 Kun Zhang,2 Lixia Gao,3 Sujuan Sun1 1Nursing Department, Hebei General Hospital, Shijiazhuang City, 050000, People’s Republic of China; 2Intensive Care Unit, Hebei General Hospital, Shijiazhuang City, 050000, People’s Republic of China; 3Geriatric Cardiovascular Department II, Hebei General Hospital, Shijiazhuang City, 050000, People’s Republic of ChinaCorrespondence: Sujuan Sun, Nursing Department, Hebei General Hospital, No. 348 heping West Road, Xinhua District, Shijiazhuang City, 050000, People’s Republic of China, Tel +86 13933093071, Email hbsunsujuan@126.comObjective: To investigate the current situation of the touch comfort of nurses in the intensive care unit (ICU) of Grade A tertiary hospitals and analyse its influencing factors, to provide a basis for formulating intervention programmes.Methods: In August 2022, 343 nurses in the ICUs of eight tertiary-level hospitals in Shijiazhuang City, Hebei Province were surveyed, and the current situation of nurses’ tactile comfort and the factors affecting it in the ICU were analysed using the Nurses’ General Information Questionnaire, Nurses’ Touch Comfort Scale, Nurses’ Humanistic Qualities Self-Assessment Scale and Nursing Work Environment Scale.Results: The mean score for the tactile comfort of ICU nurses was (5.16± 1.25). Staffing, ICU nurses’ family support, nursing work environment and nurses’ humanistic qualities were positively correlated with ICU nurses and tactile comfort, whereas job title was negatively correlated with ICU nurses and tactile comfort.Conclusion: The touch comfort of nurses in ICUs is good, and the physiological dimension is at the medium level. Nursing managers could take comprehensive measures to strengthen the cultivation of nurses’ humanistic quality, improve the nursing working environment in the ICU, improve nurses’ touch comfort and promote the improvement of nursing service.Keywords: intensive care unit, nurses, comfort with touch, the nursing work environment, nurses’ humanistic quality self-assessment scale, influencing factors